COLCHICINA: INTOXICAÇÃO E ÓBITO, RELATO DE CASO - GABRIEL, P.M.K.C.; GABRIEL, M.M.; ESCORSIN NETO, J.; LOPES, M. (Visão Acadêmica, 2004)
B. I., de 67 anos, foi internado em um hospital no interior do Estado do Paraná, apresentando dor abdominal, vômitos e diarréia intensa, vindo a falecer após 4h de internamento. Após investigação do médico sanitarista, constatou-se que a vítima havia começado tratamento com cápsulas manipuladas com o princípio ativo colchicina. Análise por cromatografia líquida de alta resolução (HPLC) indicou positividade para colchicina nas cápsulas, com concentração média de 63,48mg e negativo no material biológico da vítima. A intoxicação por colchicina foi confirmada através dos exames anátomo patológico, sintomatologia apresentada no período de internamento e a alta dosagem de colchicina encontrada nas cápsulas manipuladas e ainda disponíveis. COLCHICINE: INTOXICATION AND DEATH, CASE REPORT Abstract B. I., sixty-seven years old, was taken to a hospital with abdominal cramps, vomiting and intense diarrhoea; he died four hours after being admitted in the emergency ward. After some medical investigation, it became known that the patient had started a treatment with colchicine in capsules prepared by a pharmacist. The capsules and the autopsy materials were analysed by High Performance Liquid Chromatography (HPLC) and the analytical results for the capsules were positive for colchicine with mean concentration of 63,48mg/capsule; the analytical results for the autopsy materials were negative for colchicine. The fatal colchicine intoxication was confirmed by the anatomo-pathological exams carried out in the autopsy materials, by the sintomatology presented by the patient during his staying in the hospital and by the high concentration of colchicine found in the still remaining capsules.